The diverse role of heparan sulfate and other GAGs in SARS-CoV-2 infections and therapeutics. (1st January 2023) - Eilts, Friederike; Bauer, Sarah; Fraser, Keith; Dordick, Jonathan S.; Wolff, Michael W.; Linhardt, Robert J.; Zhang, Fuming
Abstract: In December 2019, the global coronavirus disease 2019 (COVID-19) pandemic began in Wuhan, China. COVID-19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which infects host cells primarily through the angiotensin-converting enzyme 2 (ACE2) receptor. In addition to ACE2, several studies have shown the importance of heparan sulfate (HS) on the host cell surface as a co-receptor for SARS-CoV-2-binding. This insight has driven research into antiviral therapies, aimed at inhibiting the HS co-receptor-binding, e.g., by glycosaminoglycans (GAGs), a family of sulfated polysaccharides that includes HS. Several GAGs, such as heparin (a highly sulfated analog of HS), are used to treat various health indications, including COVID-19. This review is focused on current research on the involvement of HS in SARS-CoV-2 infection, implications of viral mutations, as well as the use of GAGs and other sulfated polysaccharides as antiviral agents. Graphical abstract: Unlabelled Image